ADAR activation by inducing a syn conformation at guanosine adjacent to an editing site - Erin Doherty; Agya Karki; Xander E. Wilcox; Herra G. Mendoza; Aashrita Manjunath; Victorio Jauregui Matos; Andrew J. Fisher; Peter A. Beal (2022)
ADARs (adenosine deaminases acting on RNA) can be directed to sites in the transcriptome by complementary guide strands allowing for the correction of disease-causing mutations at the RNA level. However, ADARs show bias against editing adenosines with a guanosine 5' nearest neighbor (5'-GA sites), limiting the scope of this approach. Earlier studies suggested this effect arises from a clash in the RNA minor groove involving the 2-amino group of the guanosine adjacent to an editing site. Here we show that nucleosides capable of pairing with guanosine in a syn conformation enhance editing for 5'-GA sites. We describe the crystal structure of a fragment of human ADAR2 bound to RNA bearing a G:G pair adjacent to an editing site. The two guanosines form a Gsyn:Ganti pair solving the steric problem by flipping the 2-amino group of the guanosine adjacent to the editing site into the major groove. Also, duplexes with 2'-deoxyadenosine and 3-deaza-2'-deoxyadenosine displayed increased editing efficiency, suggesting the formation of a Gsyn:AH+anti pair. This was supported by X-ray crystallography of an ADAR complex with RNA bearing a G:3-deaza dA pair. This study shows how non-Watson-Crick pairing in duplex RNA can facilitate ADAR editing enabling the design of next generation guide strands for therapeutic RNA editing.